Physical oceanography from Video-CTD station M162_85-1 during METEOR cruise M162 (Atlantic Ocean, Gloria Fault) - Mark Schmidt; Christian Hensen (PANGAEA, 2025)
A video-guided CTD system was used on M162-cruise (06.03.- 11.04.2020, Hensen et al., 2020), to study oceanographic characteristics of the water column above the Gloria Fault system, Atlantic Ocean. The CTD (Sea-Bird Electronics, SBE9plus) was a real-time data acquisition system transmitting data via coaxial cable to the deck unit (SBE11plus). The Video-CTD rosette was equipped with additional sensors, i.e. for turbidity, O2, and CH4, to monitor fluid and gas release from the seafloor.